Factorizations of generalized Schur functions and products of passive systems - Lilleberg, L. (Methods of Functional Analysis and Topology, 2022)
Factorizations of Pontryagin space operator-valued generalized Schur functions are studied. Main tools are products of contractive operator colligations, or cascade connections of passive discrete-time systems. The well-known notion of regular factorizations of ordinary Schur functions is extended to the generalized Schur class functions by using canonical reproducing kernel Pontryagin space models. Factorizations stronger than the regular factorization are also introduced to obtain characterizations in the case where the products of observable co-isometric (controllable isometric) systems preserve the observability (controllability). These factorizations are related to backwards shift invariant regular subspaces of de Branges–Rovnyak spaces, and they can alternatively be viewed as regular factorizations of generalized Schur functions with certain extreme properties. Moreover, their properties are linked with how the optimality is preserved under the product of optimal passive systems. Досліджено факторизацію операторнозначних узагальнених функцій Шура нп просторі Понтрягіна. Основними інструментами є добутки стискаючих операторних з’єднань, або каскадних зв’язків пасивних систем з дискретним часом. Добре відоме поняття регулярних факторизацій звичайних функцій Шура поширюється на узагальнені функції класу Шура за допомогою канонічних відтворюючих ядер для моделей простору Понтрягіна. Також вводяться факторизації більш сильні, ніж звичайна факторизація, для отримання характеристик, у випадку, коли добутки спостережуваних коізометричних (керованих ізометричних) систем зберігають спостережуваність (керованість). Ці факторизації пов’язані з регулярними підпросторами просторів де Бранжа-Ровняка, які є інваріантними відносно зворотнього зсуву, і їх можна також розглядати як регулярні факторизації узагальнених функцій Шура з певними екстремальними властивостями. Крім того, їх властивості пов’язані з тим, як зберігається оптимальність відносно добутку оптимальних пасивних систем.